The Meanings of Modal Auxiliary Verbs in the Movie "The Perks of being a Wallflower" - Herlina Endah Atmaja (Lexicon, 2013)
This research attempts to investigate the meanings of modal auxiliary verbs in the movie The Perks of being a Wallflower. In particular, it aims to identify and classify the modal auxiliary verbs according to their meanings. The data used in this research were dialogues containing modal auxiliary verbs. The modal auxiliary verbs are analyzed semantically and pragmatically. Based on the data analysis, 171 modal auxiliary verbs were found in the movie. The most commonly used modal auxiliary verb in the movie is the modal auxiliary will (28.7%), followed by can (24.0%), would (21.6%), could (14.0%), should (7.0%), might (2.9%), and must (1.8%). From the 171 modal auxiliary verbs, 43 (25.1%) are used to express epistemic meanings, 23 (13.4%) are used to express deontic meanings, and 105 (61.3%) are used to express dynamic meanings. It was found in this research that the modal auxiliary verbs are most frequently used to express dynamic meanings.